Harnessing Insect Chemosensory and Mechanosensory Receptors Involved in Feeding for Precision Pest Management - Tingwei Mi; Chengwang Sheng; Cassidy Kylene Lee; Peter Nguyen; Yali V. Zhang (Life)
Chemosensation and mechanosensation are vital to insects’ survival and behavior, shaping critical physiological processes such as feeding, metabolism, mating, and reproduction. During feeding, insects rely on diverse chemosensory and mechanosensory receptors to distinguish between nutritious and harmful substances, enabling them to select suitable food sources while avoiding toxins. These receptors are distributed across various body parts, allowing insects to detect environmental cues about food quality and adjust their behaviors accordingly. A deeper understanding of insect sensory physiology, especially during feeding, not only enhances our knowledge of insect biology but also offers significant opportunities for practical applications. This review highlights recent advancements in research on feeding-related sensory receptors, covering a wide range of insect species, from the model organism Drosophila melanogaster to agricultural and human pests. Additionally, this review examines the potential of targeting insect sensory receptors for precision pest control. Disrupting behaviors such as feeding and reproduction emerges as a promising strategy for pest management. By interfering with these essential behaviors, we can effectively control pest populations while minimizing environmental impacts and promoting ecological balance.